Manajemen Harga dan Kualitas Produk Ikan Salem (Scomber japonicus) Terhadap Keputusan Pembelian Konsumen di PT. DMP - Agustin, Amanda Felen Eka; Suseno, Dewi Alima Nostalia; Widyastuti, Rida (Innovative: Journal Of Social Science Research, 2025)
This study aims to assess the impact of the price and quality of Salem fishing (Scomber japonicus) on purchasing decisions at PT. DMP, Sidoarjo. The survey was conducted with 24 respondents. The results show that the main factors influencing the purchase are the freshness, color and structure of the meat. Price plays a role, but loyalty is influenced by the perception of quality. The use of excellent handling practices and cold chain management supports quality consistency supported by long-term partnerships to stimulate raw materials. Quality consistency is key to maintaining consumer loyalty.